Looking at Bodies and Producing Images: Two Black Women’s Oppositional Practices in 2020 - Bilac Pianchão do Carmo, Daniel (2021)
In this article, we analyze the dynamics of naturalization and denaturalization of discourses encoded in images in the context of the year 2020, when discussions and protests on racial issues were triggered. We started with the productions of two black American women: Darnella Frazier, who recorded the video that showed George Floyd’s execution; and Caroline Randall Williams, who used her space in The New York Times to debate racism, body and monuments. With this empiricism, we seek to understand how the operations of the oppositional gaze prove to be productive and capable of affectation, causing reflection and mobilization around the theme in the media and in the streets, on a global scale.